2004
DOI: 10.1002/app.20579
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high rubber styrene–EPDM–acrylonitrile graft copolymer and its toughening effect on SAN

Abstract: High rubber styrene-EPDM-acrylonitrile (AES) was prepared by the graft copolymerization of styrene (St) and acrylonitrile (AN) onto ethylene-propylene-diene terpolymer (EPDM) in n-heptane/toluene cosolvent using benzoyl peroxide as an initiator. The effects of reaction conditions, such as reaction temperature, initiator concentration, EPDM content, the solvent component, and reaction time, on the graft copolymerization are discussed. In addition, according to the research on mechanical properties of the SAN/AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
0
17
0
7
Order By: Relevance
“…Figure 6 shows the SEM micrographs of impact-fractured surfaces of SAN resin (Figure 6a) and SAN/PEB-g-MAN blends containing different PEB content (Figures 6b-h). In Figure 6(a), the SAN resin fracture surface has a fragmented, flaky appearance resulting from crack break-up, which is a typical brittle characteristic, [19] so the impact energy dissipation is little. Figures 6(b) and (c) show the SEM micrographs of the fracture surface of SAN/PEBg-MAN blends containing 5 and 10 wt% PEB.…”
Section: Morphology Of Cryogenically Fractured Surfacementioning
confidence: 99%
“…Figure 6 shows the SEM micrographs of impact-fractured surfaces of SAN resin (Figure 6a) and SAN/PEB-g-MAN blends containing different PEB content (Figures 6b-h). In Figure 6(a), the SAN resin fracture surface has a fragmented, flaky appearance resulting from crack break-up, which is a typical brittle characteristic, [19] so the impact energy dissipation is little. Figures 6(b) and (c) show the SEM micrographs of the fracture surface of SAN/PEBg-MAN blends containing 5 and 10 wt% PEB.…”
Section: Morphology Of Cryogenically Fractured Surfacementioning
confidence: 99%
“…If the particle size is greater than the critical value the blends will still be a brittle and incompatible. For example, the effective toughness occurs at an optimum particle size of 0.1-1 μm for SAN [26] and when the optimum particle size of dispersed EPDM is achieved, necessary levels of adhesion with the SAN matrix is provided and effective increase of impact toughness is achieved. However, as the ratio of two polymers in blend progress toward equality, co-continuous phase is formed, Figure 7c.…”
Section: Morphology Of the Blendsmentioning
confidence: 99%
“…Moreover, many research works have revealed that the use of ST as a co-monomer in graft copolymerization systems containing a high dissimilar polarity between the rubber backbone and a monomer (e.g. MMA [17,18], glycidyl methyl methacrylate [19] and acrylonitrile [20]) can enhance the grafting yields.…”
Section: Introductionmentioning
confidence: 99%